2009
DOI: 10.1111/j.1365-2133.2009.09516.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical sodium cromoglicate relieves allergen- and histamine-induced dermal pruritus

Abstract: SCG is effective in reducing pruritus but has no effect on weals, supporting the proposition that, in the skin, SCG inhibits sensory C-fibre nerve activation rather than preventing mast cell degranulation. We suggest that topical SCG treatment, delivered in an appropriate vehicle, may be beneficial for symptomatic relief of pruritus in patients with cutaneous mastocytosis and other pruritic dermatoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 18 publications
0
32
0
2
Order By: Relevance
“…3) Successful cross-breeding of mice that spontaneously develop AA-like lesions (C3H/HeJ mice) with MC-deficient mouse strains [118] has not yet been achieved by any group. 4) Frequently employed inhibitors of MC degranulation such as cromolyn or luteolyn are not effective for all MC subsets and/or are not MC-specific, as other cell populations, including CD8+ T-cells and sensory neurons and their axons, are also affected [119][122].…”
Section: Discussionmentioning
confidence: 99%
“…3) Successful cross-breeding of mice that spontaneously develop AA-like lesions (C3H/HeJ mice) with MC-deficient mouse strains [118] has not yet been achieved by any group. 4) Frequently employed inhibitors of MC degranulation such as cromolyn or luteolyn are not effective for all MC subsets and/or are not MC-specific, as other cell populations, including CD8+ T-cells and sensory neurons and their axons, are also affected [119][122].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with predominantly gastrointestinal symptoms but also with symptoms of musculoskeletal pain, fatigue, and headache, therapy with oral and inhaled sodium cromolyn may be tried, as noted in a case report [43]. An exploratory study in 20 allergic and 40 nonallergic individuals in whom aqueous cream containing sodium cromoglycate was applied before skin prick test with allergens, codeine, and histamine suggests that this medication may be effective in reducing pruritus [44]. In another trial, the lipid raft modulator miltefosine showed a trend toward reducing the volume of wheals in 39 adult patients with skin involvement of mastocytosis after topical therapy [45], but it cannot yet be recommended.…”
Section: Therapy For Cutaneous and Indolent Systemic Mastocytosismentioning
confidence: 91%
“…B. Loratadin, Cetirizin, Desloratadin, Levocetirizin, täglich oder bei Bedarf) meist gut beherrschbar [1,4]. Weiterhin haben sich topische Substanzen wie Polidocanol oder Cromoglycinsäure in der antipruritischen Therapie bewährt [27]. Großflächige symptomatische Plaques und Knoten sowie solitäre Mastozytome können kurzfristig mit topischen Kortikosteroiden behandelt werden.…”
Section: Therapieunclassified